Heat-assisted machining - Amin, A. K. M. Nurul; Ginta, Turnad Lenggo (Elsevier Ltd., 2014)
Heat-assisted machining, which is popularly known as hot machining, has emerged as an alternative method of machining for improving the machinability of difficult-to-cut metals and alloys. This technique has been under consideration since the late nineteenth century. It was observed that metals tend to deform more easily when heated, thus enhancing machinability. Hot machining found widespread application in the manufacture of engineering components in the late twentieth century, a century after it was first introduced. The principle behind hot machining is to increase the difference in hardness of the cutting tool and workpiece, leading to reduced component forces, improved surface finish, and longer tool life.